2012
DOI: 10.1182/blood-2012-02-408799
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms and inherited risk of chronic lymphocytic leukemia among African Americans

Abstract: The incidence of chronic lymphocytic leukemia (CLL) is significantly lower in African Americans than whites, but overall survival is inferior. The biologic basis for these observations remains unexplored. We hypothesized that germline genetic predispositions differ between African Americans and whites with CLL and yield inferior clinical outcomes among African Americans. We examined a discovery cohort of 42 African American CLL patients ascertained at Duke University and found that the risk allele frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…A recent study looked at the frequency of the known GWAS alleles in an African-American population and found that most of these alleles were less common in African-American CLL patients compared with Caucasian patients [Coombs et al 2012]. Furthermore the allele frequency was not different among African-Americans with CLL compared with African-American control populations, suggesting that these alleles are not major contributors to disease risk in African-Americans [Coombs et al 2012]. Further work will be required to define genetic risk in African-Americans as well as other ethnic groups.…”
Section: Moving To Genomewide Analyses: Associationmentioning
confidence: 99%
“…A recent study looked at the frequency of the known GWAS alleles in an African-American population and found that most of these alleles were less common in African-American CLL patients compared with Caucasian patients [Coombs et al 2012]. Furthermore the allele frequency was not different among African-Americans with CLL compared with African-American control populations, suggesting that these alleles are not major contributors to disease risk in African-Americans [Coombs et al 2012]. Further work will be required to define genetic risk in African-Americans as well as other ethnic groups.…”
Section: Moving To Genomewide Analyses: Associationmentioning
confidence: 99%
“…Together with the MD Anderson Cancer Center, we previously found that African Americans with CLL have inferior clinical outcomes compared to Whites with CLL (Falchi et al , ), although the underlying reason for this is unknown (Coombs et al , ). Our current work demonstrates that African Americans with CLL had lower CD5 expression than Whites with CLL, suggesting that at least part of the differences in clinical outcomes may be related to CD5 expression and downstream signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Data that supported differential genetic risk for CLL exists between Black and White CLL patients led to the belief that biological differences might exist between W and NW CLL patients [15]. In fact, Falchi and colleagues analyzed outcomes of untreated African American patients as compared with non-black reference patients [16].…”
Section: Discussionmentioning
confidence: 99%